The Gene vepN Regulated by Global Regulatory Factor veA That Affects Aflatoxin Production, Morphological Development and Pathogenicity in Aspergillus flavus - Jia Xu; Mengqi Jiang; Peng Wang; Qing Kong (Toxins, 2024)
Velvet (VeA), a light-regulated protein that shuttles between the cytoplasm and the nucleus, serves as a key global regulator of secondary metabolism in various Aspergillus species and plays a pivotal role in controlling multiple developmental processes. The gene vepN was chosen for further investigation through CHIP-seq analysis due to significant alterations in its interaction with VeA under varying conditions. This gene (AFLA_006970) contains a Septin-type guanine nucleotide-binding (G) domain, which has not been previously reported in Aspergillus flavus (A. flavus). The functional role of vepN in A. flavus was elucidated through the creation of a gene knockout mutant and a gene overexpression strain using a well-established dual-crossover recombinational technique. A comparison between the wild type (WT) and the ΔvepN mutant revealed distinct differences in morphology, reproductive capacity, colonization efficiency, and aflatoxin production. The mutant displayed reduced growth rate; dispersion of conidial heads; impaired cell wall integrity; and decreased sclerotia formation, colonization capacity, and aflatoxin levels. Notably, ΔvepN exhibited complete growth inhibition under specific stress conditions, highlighting the essential role of vepN in A. flavus. This study provides evidence that vepN positively influences aflatoxin production, morphological development, and pathogenicity in A. flavus.